Mechanism of joint physical layer and MAC layer for handling multi-TRP UL overlapping transmissions - JING Xiaorong; XIONG Jie; SUN Jian; CHEN Qianbin (Tongxin xuebao)
To address the severe uplink (UL) overlapping transmission problem caused by multi-timing advance (multi-TA) in multiple transmission reception point (multi-TRP) scenario with non-ideal feedback, where existing protocols were difficult to handle effectively, a novel UL overlapping transmission handling mechanism was proposed by jointly improving physical layer multiplexing technology and medium access control (MAC) layer token bucket technology. The novel mechanism enhanced the identification process of overlapping channels at the physical layer, revised the multiplexing requirements and rules, and fed the multiplexing and overlapping information from the physical layer back to the MAC layer. Simultaneously, it optimized the token bucket technique in the MAC layer. Comparative simulations between the proposed mechanism and the processing mechanisms in existing protocols show that, in non-overlapping and overlapping logical slot scenarios, the actual number of the reused physical uplink control channel (PUCCH) performance has improved by an average of 57.58% and 49.40%, the actual available resource quantity performance of the physical uplink shared channel (PUSCH) has improved by an average of 12.09% and 26.03%, the actual occupied resource quantity of the highest priority logical channel has improved by an average of 33.33% and 45.48%.